INVESTIGATION OF A CA-DEPENDENT INDUCER ON HEMOSTASIS PROPERTIES IN LABORATORY ANIMALS - V. S. Orlova; E. V. Orlova; O. V. Petrova; Ya. M. Stanishevskiy (Разработка и регистрация лекарственных средств)
The effect of a new drug - selective activator of Ca-dependent NO-synthase on the processes of hemostasis in norm and type 2 diabetes in laboratory animals is shown in this paper.